Analisis Kompetensi Mahasiswa D3 Jurusan Teknik Otomotif - Alim Kusuma; Wawan Purwanto (AEEJ : Journal of Automotive Engineering and Vocational Education, 2021)
Education is a process to optimize one's potential in certain ways to achieve certain goals. Every university has graduate competency standards that every student must have. Graduate competencies are made based on the expected graduate profile of each study program, including the automotive engineering study program. Based on data from sia2.unp.ac.id the comparison between the number of students entering and graduating D3 Automotive Engineering UNP students in 2014 to 2017 was 225 versus 101. This study used a quantitative descriptive method involving 75 students as respondents. The purpose of this study is to describe the abilities possessed by D3 students of the Automotive Engineering Department in 2020. The highest percentage of student competencies is at the B+ score, which is 25%, followed by A-, A, E, B, B-, C, C, C+. , and D, respectively, the percentages are 18%, 14%, 11%, 8%, 6%, 6%, 6%, 3%, 3%. Pendidikan adalah proses untuk mengoptimalkan potensi diri dengan cara-cara tertentu untuk mencapai tujuan tertentu. Setiap perguruan tinggi memiliki standar kompetensi lulusan yang wajib dimiliki oleh setiap mahasiswa. Kompetensi lulusan dibuat berdasarkan profil lulusan yang diharapkan setiap program studi, termasuk program studi teknik otomotif. Berdasarkan data dari sia2.unp.ac.id perbandingan antara jumlah mahasiswa masuk dan lulus mahasiswa D3 Teknik Otomotif UNP tahun masuk 2014 sampai 2017 adalah 225 berbanding 101. Penelitian ini menggunakan metode deskriptif kuantitatif yang melibatkan 75 orang mahasiswa sebagai respondenya. Tujuan dari penelitian ini adalah untuk memaparkan kemampuan yang dimiliki mahasiswa D3 Jurusan Teknik Otomotif tahun masuk 2020. Persentase kompetensi mahasiswa paling tinggi berada pada nilai B+ yaitu 25% disusul A-, A, E, B, B-, C, C-, C+, dan D yang berturut turut presentasenya 18%, 14%, 11%, 8%, 6%, 6%, 6%, 3%, 3%.